A series of enzyme-controlled-release polymer-platinum-based drug conjugates for the treatment of gastric cancer. (July 2017) - Shi, Tianyi; Gu, Lianshuai; Sun, Yu; Wang, Senlin; Zhang, Xiangyang; Zhu, Jin; Sun, Baiwang
Graphical abstract: Highlights: We use the MGC803 and MKN28 cells to verify the specificity and cytotoxicity of the polymer drugs. The design of the structure of polymer drugs by using a multifunctional octapeptide to conjugate with the polymers, platinum-based drugs and the fluorescence signal. Due to the hydrophily of the MPEG, 4-arm-PEG and octapeptide, the synthesis process could perform into the aqueous solution, and purification route could take advantage of the ultrafiltration which was an efficient separation method. Abstract: Platinum-based drugs are widely used as a master key in the multiple cancer therapies, while limited by the adverse side effects during the in vivo circulation. To settle the aforementioned problems, we prepare a series of polymer-platinum conjugates by utilizing the "stealth" polyethylene glycol and legumain-cleavable oligopeptide. We select MGC803 cells overexpressing the legumain and MKN28 cells negatively expressing the legumain as well as the normal stomach cells to compose the test groups. In vitro cytotoxicity studies indicate the polymer-platinum conjugates with the assistance of Ala-Ala-Asn tripeptide can effectively inhibit the growth of MGC-803 cells than control groups. Meanwhile, the MPEG polymer show better anticancer ability than 4-arm-PEG polymer. However, in the group of MKN28 cells, both polymer-platinum conjugates express weak cytotoxicity due to lacking of the mediation of legumain. Hence, the synthesized polymer-platinum conjugates exhibiting great potential in avoiding the side effects and enhancing the therapy ability will be valuable for the platinum-cancer therapy.